A Review on the Use of Burning Rate Suppressants in AP‐Based Composite Propellants - Xu, Shuang; Pang, Ai‐Min; Wang, Yue; Pan, Xin‐Zhou; Li, Shang‐Wen; Li, Hai‐Tao; Kong, Jie (Propellants, explosives, pyrotechnics, 2022)
Ammonium perchlorate (AP) is the most widely used oxidant in composite propellants. Propellants based on AP usually have a high burning rate, but in some applications, it is necessary to have a slower burning rate. The functional additives, which can reduce the burning rate of propellants, were named coolants, burning rate suppressants (BRSs), burning rate depressants, or burning rate inhibitors. This paper introduced different types of BRSs, such as amide‐based compounds, cyclic azines, quaternary ammonium salts, metal salts, etc., their mechanism and development in AP‐based composite propellants. For organic amines, the burning rate trend is as follows: biuret<melamine<oxamide<urea<base. Cyclic azines are special organic amines which form large, thermally stable cyclic azines in addition to common low‐molecular‐weight gases NH3, CO2, HCN, and N2O when heated. With the smallest addition but the highest effect, quaternary ammonium salts will not reduce the specific impulse of the propellant, nor do they interfere with cure reaction or adversely affect the physical properties of the cured propellant. Metal salts reduce the burning rate by forming more stable substances than HClO4 with AP. The mechanism of BRSs is complicated, but all of them can be explained based on AP deflagration. At last, the development trend of efficient BRSs was discussed, the preparation of liquid BRSs and the combination of AP bonding agents with BRSs were both first proposed, which worth further research in the future.